STUDI FENOMENOLOGI KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RSUD ARIFIN ACHMAD PEKANBARU - Dwi ' Hagita; Bayhakki ' '; Rismadefi ' Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Chronic renal failure is showed by the inability of the kidneys in maintaining homeostasis of body. End Stage Renal Disease (ESRD) patients should use a renal replacement therapy as the options to maintain body functions. Currently most used therapy is hemodialysis therapy. This research aimed to determine quality of life chronic renal failure which patients undergoing hemodialysis therapy at Arifin Achmad hospital. This research using qualitative methode with phenomenological approach. Data obtained from a dept interviews with 8 participants that were 2 males and 6 females, 27-60 years old, and have been undergoing hemodialysis for 2-10 years. Interviews results were analyzed by using Colaizzi methode. The result showed eigth themes: decrease in the fulfillment of physiological needs, changes in psychological response, increased spiritual response, the change of social interaction, support needed, change the economic status, the quality of life of physical and psychological decreases, and adaptation. Based this research it can be concluded that changes in the physical, psychological, social economic, and spiritual hemodialysis patients. Holistic social support is important to increased quality of life patient with chronic failure kidney.